SURVEI MINAT MASYARAKAT DALAM BERAKTIVITAS OLAHRAGA DI RUANG TERBUKA KOTA SALATIGA TAHUN 2022 - Jihan Hasna Fadillah; Anggit Wicaksono (Unnes Journal of Sport Sciences, 2023)
The lack of sports facilities and infrastructure owned by Sidomukti District, Salatiga City, makes people have to be good at utilizing the surrounding environment for sports activities and in between the busyness of the community makes the reason for researchers to research about people's interest in sports activities in open spaces. This research method uses survey research with a descriptive quantitative approach type. The data was taken using an online questionnaire. The population in this study was all the people of Sidomukti District, Salatiga City, which amounted to 44,946 people and the research sample was 150 samples using accidental sampling techniques. The variable used is the public's interest in sports activities in open spaces, Sidomukti District, Salatiga City. The results of the research on public interest in sports activities in open spaces of Sidomukti District, Salatiga City in 2022 are categorized as very high with a result of 81.29%. Calculations based on intrinsic interest of 83.87% belong to the very high category, and extrinsic interest of 78.70% belongs to the high category. Public interest in sports activities in open spaces, Sidomukti District, Salatiga City is very high with a result of 81.29%. Suggestions: 1) for the government of Sidomukti Subdistrict, Salatiga City, to continue to pay attention to the community so that the community can maintain interest in sports activities in open spaces 2) for people in Sidomukti District, Salatiga City to be able to maintain interest in sports activities in open spaces.